Cecha lęku i nadzieja na sukces jako korelaty partycypacji społecznej studentów - Rękosiewicz, Małgorzata (Studia Edukacyjne, 2024)
The aim of the study was to verify the hypothesis about the trait of anxiety and hope for success as correlates of students’ social participation. The Social Participation Questionnaire, the Hope for Success Questionnaire and the STAI State-Trait Anxiety Inventory were used. The study participants were 209 students aged 19-25. It was shown that a higher level of trait anxiety was associated with a lower level of moratorium and transitive orientation, and a higher level of hope for success was associated with a higher level of transitive orientation.